Four-dimensional context of Earth's supercontinents - Evans, D.; Li, Zheng-Xiang; Murphy, J. (2016)
The supercontinent-cycle hypothesis attributes planetary-scale episodic tectonic events to an intrinsic self-organizing mode of mantle convection, governed by the buoyancy of continental lithosphere that resists subduction during closure of old ocean basins, and consequent reorganization of mantle convection cells leading to opening of new ocean basins. Characteristic timescales of the cycle are typically 500-700 myr. Proposed spatial patterns of cyclicity range from hemispheric (introversion) to antipodal (extroversion), to precisely between those end-members (orthoversion). Advances in our understanding can arise from theoretical or numerical modelling, primary data acquisition relevant to continental reconstructions, and spatiotemporal correlations between plate kinematics, geodynamic events and palaeoenvironmental history. The palaeogeographic record of supercontinental tectonics on Earth is still under development. The contributions in this special publication provide snap-shots in time of these investigations and indicate that Earth's palaeogeographic record incorporates elements of all three endmember spatial patterns.